Розробка інформаційної системи підтримки обслуговування клієнтів велобаз - Шапаренко, М. Е. (ХНУРЕ, 2023)
This workos devoted to the analysis of bike rent service subject area and business processes, database design and realization, REST API design and development for integration with web-interface. The main development stages of the informational system are considered.